Sur la « désobéissance poétique » - Tobias Etienne-Greenwood (Amnis)
At the end of 2019, a collective of artivists was formed in the province of Mendoza in reaction to the attempt to modify law 7722, which protects water and prevents, most extractivist projects in the region. Quickly, this collective took a leading role in the "Mendozaguazo" by spreading the struggle on social networks but also by intervening in the public space in actions sometimes described as "poetic disobedience". Based on data collected on the collective's social networks and meetings with activists, this paper presents itself as a moment of dialogue between the theories of civil disobedience with perspectives informed by the poetic-aesthetic practice of the members of this collective.